How Does the Use of Dating Apps Relate to Physical Health Behaviors and Mental Health? A Narrative Review - Dżumaga, Justyna; Janiszewska, Michalina; Sobkowiak, Maciej; Sobkowiak, Paulina; Jusiak, Justyna; Łuczak, Janusz; Łuczak, Jeremi; Łazik, Maria; Dybowska, Roksana; Walaszek, Marta (Journal of Education, Health and Sport, 2026)
Dating applications have become a central component of contemporary romantic and social interactions, particularly among adolescents, young adults, and emerging adults. While these platforms offer opportunities for social connection, accumulating evidence suggests that dating app use may be associated with a range of mental health outcomes and physical health–related behaviors. Research in this area remains fragmented, with findings dispersed across psychological, behavioral, and public health disciplines. Aim. The aim of this narrative review is to synthesize and critically analyze existing research on the relationship between dating app use, mental health outcomes, and physical health behaviors. Material and methods. A narrative review of peer-reviewed literature was conducted using articles provided by the author. The included studies encompassed cross-sectional, longitudinal, diary-based, and review designs examining dating app use in relation to mental health indicators. Results. The reviewed literature indicates that dating app use is associated with diverse mental health outcomes, including depressive symptoms, anxiety, loneliness, body dissatisfaction, and self-esteem fluctuations. Additionally, dating app engagement has been linked to several physical health behaviors, such as risky sexual practices, sexually transmitted infection risk, alcohol and substance use, sleep disturbances, and unhealthy weight-control behaviors. Conclusions. Dating app use appears to be meaningfully related to both mental health and physical health behaviors, although the direction and strength of these associations vary across populations and study designs. Further longitudinal and theory-driven research is needed to clarify causal mechanisms and to inform health education, prevention, and public health interventions.